Prooxidant activity-based guideline for a beneficial combination of (−)-epigallocatechin-3-gallate and chlorogenic acid. (30th August 2022) - Yang, Lumin; Jia, Lijie; Li, Xiuli; Zhang, Ke; Wang, Xiaoxiao; He, Yufeng; Hao, Meng; Rayman, Margaret P.; Zhang, Jinsong
Graphical abstract: Highlights: Prooxidant activities of EGCG are much stronger than those of chlorogenic acid (CGA). CGA and EGCG synergistically increase hydrogen peroxide. CGA decreases EGCG/copper-derived hydroxyl radicals. CGA suppresses toxicity but doesn't perturb AMPK or Nrf2 induced by high-dose EGCG. Low-dose EGCG together with CGA synergistically activates AMPK and Nrf2. Abstract: In the current study, the prooxidant activities of (-)-epigallocatechin-3-gallate (EGCG) and chlorogenic acid (CGA) were systematically compared both in multiple in vitro models and in mice. At equimolar concentrations in vitro and in vivo, EGCG displayed powerful prooxidant effects though CGA exhibited none. In vitro, though CGA and EGCG synergistically produced hydrogen peroxide, CGA was able to scavenge hydroxyl radicals generated by EGCG/copper. Consistent with the selective modulation of reactive oxygen species produced from EGCG, CGA lowered hepatotoxicity but did not perturb hepatic AMPK activation nor the increase of hepatic Nrf2-associated proteins induced by high-dose EGCG. CGA, along with low-dose EGCG, synergistically activated hepatic AMPK and increased hepatic Nrf2-associated proteins without causing toxicity in mice. This proof-of-principle study suggests that polyphenols with potent prooxidant activities (e.g., EGCG) together with antioxidant polyphenols with noticeably low prooxidant activities (e.g., CGA) may yield health benefits with a low risk of side effects.